Tuning the transcription and translation of L-amino acid deaminase in Escherichia coli improves α-ketoisocaproate production from L-leucine. - Yang Song; Jianghua Li; Hyun-Dong Shin; Long Liu; Guocheng Du; Jian Chen (PLoS ONE)
α-Ketoisocaproate (KIC) is used widely in the pharmaceutical and nutraceutical industries. In previous studies, we achieved a one-step biosynthesis of KIC from l-leucine, using an Escherichia coli whole-cell biocatalyst expressing an l-amino acid deaminase (l-AAD) from Proteus vulgaris. Herein, we report the fine-tuning of l-AAD gene expression in E. coli BL21 (DE3) at the transcriptional and translational levels to improve the KIC titer. By optimizing the plasmid origin with different copy numbers, modulating messenger RNA structure downstream of the initiation codon, and designing the sequences at the ribosome binding site, we increased biocatalyst activity to 31.77%, 24.89%, and 30.20%, respectively, above that achieved with BL21/pet28a-lad. The highest KIC titers reached 76.47 g·L-1, 80.29 g·L-1, and 81.41 g·L-1, respectively. Additionally, the integration of these three engineering strategies achieved an even higher KIC production of 86.55 g·L-1 and a higher l-leucine conversion rate of 94.25%. The enzyme-engineering strategies proposed herein may be generally applicable to the construction of other biocatalysts.